Comparative analysis of yield and quality traits in two elite Chinese wheat varieties under varied nitrogen fertilizations and environmental conditions - Kaijie Xu; Zhaoxing Zhang; Wenfei Tian; Lei Zhi; Junliang Yan; Jun Yan; Chengyan Zheng; Yan Zhang; Yong Zhang; Zhonghu He (Wiley, 2024)
Background and Objectives: This study explored the impact of nitrogen (N) application on yield and breadmaking as well as arabinoxylan (AX) content of wheat varieties Zhongmai 578 and Jimai 22 across varied environments, aiming to optimize N levels for improved outcomes. Findings: Significant N effects were observed on yield, flour properties, and breadmaking quality traits. Both varieties displayed high yield potential and stability, with Zhongmai 578 excelling in thousand kernel weight and Jimai 22 in spike number. Optimal N rates varied by location, with some achieving peak yields at reduced N levels. Processing traits like dough properties and bread-making quality were influenced by E × N interactions. Arabinoxylans profiles was not affected by different N input. Conclusions: Customizing N applications to specific environment is critical for maximizing wheat yield potential and quality. Environmental considerations are integral for achieving desired processing traits and yield, highlighting the need for tailored N strategies in wheat cultivation. Significance and Novelty: This study emphasizes the importance of site-specific optimization of N levels for enhanced yield and processing quality. It offers novel insights into site-specific N management, showcasing its relevance in modern agricultural practices for sustainable crop production.